1998
DOI: 10.1016/s0014-5793(98)00908-9
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic repair of oxidative damage to human apolipoprotein A‐I

Abstract: Oxidative damage to apolipoprotein A-I that occurs in vivo commonly involves methionine oxidation, and is accompanied by alterations in structure, lipid association, and cholesterol efflux function. We have used the enzyme peptide methionine sulfoxide reductase (PMSR) to reverse this damage, and shown by a variety of criteria that enzyme treatment restores the primary, secondary, and tertiary structure and lipid association characteristic of the native unoxidized protein.Lipid-associated as well as lipid-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 19 publications
(18 reference statements)
5
36
0
Order By: Relevance
“…This observation further supports the anti-oxidative properties of Met in proteins and peptides, as discussed by others [12,38,39]. Recently it has been shown that oxidized Met""# and Met"%) in lipid-free as well as in lipid-associated apo A-I can be reduced to Met in itro by peptide Met(SO) reductase [40], suggesting that the enzymic reduction of oxidized apo A-I could restore its biological activity.…”
Section: Discussionsupporting
confidence: 86%
“…This observation further supports the anti-oxidative properties of Met in proteins and peptides, as discussed by others [12,38,39]. Recently it has been shown that oxidized Met""# and Met"%) in lipid-free as well as in lipid-associated apo A-I can be reduced to Met in itro by peptide Met(SO) reductase [40], suggesting that the enzymic reduction of oxidized apo A-I could restore its biological activity.…”
Section: Discussionsupporting
confidence: 86%
“…Several protein substrates for PMSR have been investigated in animal and microbial systems. These include the ␣-1-proteinase inhibitor (Abrams et al, 1981), calmodulin (Sun et al, 1999), apolipoprotein A1 (Sigalov and Stern, 1998), and ␣/␤-spore proteins (Hayes et al, 1998). We found that both plant PMSR isoforms were able to repair the bovine oxidized ␣-1-proteinase inhibitor protein at rates comparable to those reported in the literature for non-plant PMSRs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the above reaction is slow, although it is accelerated by unknown factor(s) in liver (154), and a slow reduction could still be important under circumstances such as in an atherosclerotic vessel where the average residence time of lipoproteins is long. Peptide methionine sulfoxide reductase acts on methionine sulfoxides in lipid-free and lipid-associated apolipoprotein A-I, suggestive of enzymatic repair of the oxidized protein (850), although it remains unclear whether the cellular sulfoxide reductase can act on extracellular apolipoprotein(s).…”
Section: Throughout the Cellmentioning
confidence: 99%